ANALISIS KAPASITAS DAYA DUKUNG AKSIAL TIANG TEKAN DAN PENURUNAN PONDASI BORED PILE MENGGUNAKAN METODE ELEMEN HINGGA (STUDI KASUS: PEMBANGUNAN STADION UTAMA SUMATERA) - Annisa Suci Rizky; Ika Puji Hastuty; Syiril Erwin Harahap (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Bored pile foundations are one type of deep foundation used to support axial loads in building construction. This study aims to analyze the ultimate bearing capacity and settlement of a single bored pile foundation in the North Sumatra Main Stadium Project located in Batang Kuis District, Deli Serdang Regency, North Sumatra Province. The analysis was carried out on a bored pile with a diameter of 80 cm using three methods, namely the Chin Method, the Mazurkiewicz Method, and the Finite Element Method (FEM). The data used in this study were obtained from the Static Loading Test (SLT).The results indicate differences in the ultimate bearing capacity (Qu) and foundation settlement values produced by each method due to variations in their approaches to interpreting the load-settlement relationship. The Chin Method produced the highest Qu value of 617 tons with a settlement of 75 mm, indicating a more optimistic result and serving as the upper bound. The Mazurkiewicz Method produced a Qu value of 590.65 tons with a settlement of 60 mm, while the FEM analysis produced a Qu value of 600 tons with a settlement of 65 mm. Based on these results, the Mazurkiewicz Method is considered sufficiently representative because it provides values between conservative and optimistic approaches. Therefore, the use of more than one analysis method is highly recommended to obtain more accurate and reliable results in bored pile foundation design.